Reflections on Navigating Climate's Human Geographies. Issue 1 (March 2019) - Bulkeley, Harriet
In this reflection, I take up a variety of open questions and remaining concerns raised by the set of commentaries concerning the implications of the paper for: how we regard climate change as an issue; how knowledge systems might be changed to enable more diverse ways of knowing climate change to take root; and for its politics.